RELIGION AND POWER: The Comparative Dynamics of Political Islam in Malaysia and Indonesia - Muharam, Moch Mubarok; Widodo, Bambang Sigit; Febriansyah, Muhammad; Meutia, Fadhillah Sri (State Islamic University (UIN) of Sunan Ampel Surabaya, 2026)
This study compares the dynamics of political Islam in Malaysia and Indonesia, focusing on the interaction between Islamic discourses and state–religion relations. Using a qualitative comparative approach, it combines political culture and media analysis with interviews involving representatives of major Islamic organizations, including the Front Persatuan Islam, PBNU, Forum Umat Islam, UMNO, and PAS. The findings reveal contrasting trajectories of political Islam. In Indonesia, decentralization enables diverse Islamic expressions, with Islamism emerging primarily from civil society and often driven by public dissatisfaction with government. In Malaysia, political Islam is shaped by state institutions and Malay-Muslim nationalism, allowing Islamic elites to consolidate political dominance through legal and policy frameworks. These contrasting patterns demonstrate how political Islam functions both as a strategy of political power and a challenge to democratic resilience. The study contributes to debates on religion–politics relations in post-colonial democracies and the evolving role of Islamic authority in the public sphere.